Divisão de trabalho em anteras de Microlicia cordata (Spreng.) Cham. (Melastomataceae) - Velloso, Mariana de Souza Carvalho (2017)
Microlicia stands out among the Melastomataceae because it presents well pronounced heterantry, characteristic that is usually associated as a solution to the "pollen dilemma". Since pollen is the only resource offered in these species, its use in feeding pollinators decreases the number of viable gametes for reproduction. Thus, there would be a division of labor in plants with heterantry, in which the anthers would have different functions, one would be used to feed the bees and another would act in the pollination. Microlicia cordata, an abundant species in the study area, has two cycles of stamens, the antesepalous cycle (pollination) with magenta anthers and the antepetalous cycle (feeding) with yellow anthers. In this study, the division of labor between the anthers was analyzed using different parameters involving the anatomy and morphology of anthers and pollen grains, quantity and viability of pollen grains as well as coloring of floral structures. It has been found that the anthers of the pollination stamens are larger than the anthers of the feeding stamens, although they are similar anatomically. There is a difference in the amount of pollen grains produced in the anthers of the different cycles, but there is no difference in viability. Pollen grains with little or no cytoplasmic content were observed in the anthers of both cycles. Color analysis showed that anthers of pollination stamens have less contrasting color to the corolla, and are probably less attractive to visitors. However, the anthers of the feeding stamens and the ventral appendage of the connective of the pollinating stamens have greater contrast with the corolla, which allows to conclude that they reflect the same color to the pollinators. These results support the model of division of labor between anthers, particularly related to the quantity of pollen grains available and the coloring of floral pieces.